Operando Formation of Van der Waals Heterostructures for Achieving Macroscale Superlubricity on Engineering Rough and Worn Surfaces. (22nd January 2022) - Li, Ruiyun; Yang, Xing; Zhao, Jun; Yue, Chengtao; Wang, Yongfu; Li, Jiangong; Meyer, Ernst; Zhang, Junyan; Shi, Yijun
Abstract: Macroscale superlubricity breakdown of lubricating materials caused by substrate surface roughening and mechanochemical modification poses great challenges for their practical tribological applications. Here, a facile way is reported to access robust macroscale superlubricity in a vacuum environment, via the operando formation of graphene/transition‐metal dichalcogenide (TMDC) heterostructures at wear‐induced rough surfaces. By trapping active amorphous carbon (a‐C) wear products between TMDC flakes, the sandwich structures readily transform into graphene/TMDC heterostructures during running‐in stage, based on shear‐induced confinement and load‐driven graphitization effects. Then they assemble into multipoint flake‐like tribofilms to achieve macroscale superlubricity at steady stage by reducing contact area, eliminating strong cross‐interface carbon–carbon interactions and polishing a‐C rough nascent surface. Atomistic simulations reveal the preferential formation of graphene/TMDC heterostructures during running‐in stage and demonstrate the superlubric sliding of TMDCs on the graphene. The findings are of importance to achieve robust superlubricity and provide a good strategy for the synthesis of other van der Waals heterostructures. Abstract : By trapping active amorphous carbon wear products between transition‐metal dichalcogenide (TMDC) flakes, the sandwich structures readily transform into graphene/TMDC heterostructures during running‐in stage, based on shear‐induced confinement and load‐driven graphitization effects. Macroscale structural superlubricity (0.006) is achieved at steady stage by the graphene/TMDC heterostructures assembled in multipoint flake‐like tribofilms.